Shadow banking: Regulatory Reform and Its Effectiveness - V. M. Usoskin (Финансы: теория и практика)
Over the past three decades, a large group of non-bank financial institutions has been formed in the world economy. These institutions fall outside the realm of traditional banking and take an active part in the lending processes of economic turnover entities. The activities of these institutions, called the shadow banking system (SBS), led to an increase in systemic risks and had a negative impact on the state of the global financial system. This was distinctly displayed during the global financial crisis of 2007–2009. The subject of this article is a series of measures taken by the international and national financial control bodies after the financial crisis to eliminate most risky aspects of shadow banking and to strengthen the system of financial oversight and monitoring. The final aim of the analysis is to evaluate effectiveness of the measures on strengthening control and limiting risks applied by the control bodies of the G-20 countries in the course of the reform to enterprises of the traditional and shadow sectors of the financial system. The results of the analysis show that the reform strengthened positions of traditional banks and improved their ability to resist financial shocks. As to the shadow banking sector, contrary to the statements of the initiators of the reform the regulative measures did not eliminate the systemic risks peculiar to nonbank financial institutions and did not stop their growing activities. This situation threatens the stability of the global financial system and a possibility of a new financial slump retains.